Lean Tools Application Failure - Sorooshian, Shahryar; Ze En, Ler; Mohd Ghazali, Maarof; Adeleke, A. Q. (Serials Publications Pvt. Ltd., 2017)
There are less understanding of the large selection of lean tools and the management team of the companies does not have the sufficient confident in selecting a suitable lean for their companies. Lean tools provide additional value to the business and end users by reducing inefficient practices and improving the rate of product output. The purpose of this research is to provide lean area a clearer standardized process for easier implementation. This can be done by using Risk Priority Number (RPN) to quantify the risk of failure of lean tools for their implementation in service organizations. RPN method is used to identify and figure out the critical risk that exists in service industries brought by the application of lean tools. This research objective is to identify the list of lean tools for service industries and to mathematically analyze the risk of failure of lean tools application for service industries in Malaysia.